3D printed frame for CubeSat applications for low-Earth orbit mission. (2017) - Ampatzoglou, Andreas; Tsantzalis, S.; Mazarakos, Dimitrios E.; Kostopoulos, V.
In this work, an innovative 3D printing cube-satellite frame is presented. The key innovative solution proposed deals with the replacement of the typical aluminium frame, made of several aluminium parts mechanically joined together, by a 3D printed frame made of polyetherimide (PEI), which may withstand the structural as well as the thermal loads developed during the mission. The CubeSat structure is designed and analysed for all required mechanical loads of a low orbital mission. An orbital/thermal analysis regarding the specific low orbital mission profile was also considered. The proposed 3D printed CubeSat frame includes also a thermal management system that offers to the electronic equipment further cooling support. The CubeSat structure can be easily manufactured using 3D printing technology. The frame can be produced as monocoque structure, reducing the assembled parts, the developing cost and the elapsed time. Following the current methodology, it was proven that the structural requirements regarding the qualification tests and standards meet the functional specifications of a convectional CubeSat. Using 3D printing, a final CubeSat frame weight of 80 grams was concluded which is 50% lighter compared against the state of the art aluminium one.